2021
DOI: 10.7860/jcdr/2021/47073.14763
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Total Thiols and Total Thiol/Albumin Ratio in Patients Suffering from Depression

Abstract: Introduction: Increased oxidative stress has been reported in patients who suffer from depressive disorders. Albumin acts as a target for plasma protein oxidation during oxidative stress. The plasma thiols act as significant in vivo antioxidants. Major SH-groups are found on the surface of albumin molecules. Since depressive disorders are related to oxidative stress. Only a few studies have been done that correlate plasma total thiols with major depressive disorder. The authors intended to draw a relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies have identified decreased thiol groups in patients with MDD or depressive symptoms (Beğinoğlu et al, 2023;Roomruangwong et al, 2017;Tuncay et al, 2023). Conversely, several studies have detected elevations in -SH groups in patients with depression and cognitive impairment, suggesting that increased O&NS levels resulted in increased plasma thiols (Gałecki et al, 2013;Karaaslan et al, 2018;Sundaram and Prabhu, 2021). The consequence is a lack of consensus concerning the status of -SH groups in MDD.…”
Section: Findings Not In Accordance With the A Priori Hypothesismentioning
confidence: 99%
“…Previous studies have identified decreased thiol groups in patients with MDD or depressive symptoms (Beğinoğlu et al, 2023;Roomruangwong et al, 2017;Tuncay et al, 2023). Conversely, several studies have detected elevations in -SH groups in patients with depression and cognitive impairment, suggesting that increased O&NS levels resulted in increased plasma thiols (Gałecki et al, 2013;Karaaslan et al, 2018;Sundaram and Prabhu, 2021). The consequence is a lack of consensus concerning the status of -SH groups in MDD.…”
Section: Findings Not In Accordance With the A Priori Hypothesismentioning
confidence: 99%